MANAJEMEN PENGEMBANGAN GURU - Ipong Dekawati (Jurnal Cakrawala Pendidikan, 2011)
Abstract: The Teacher Development Management. The research is aimed at analyzing the effects of further study, profession training, participation in scientific forums, further study and profession training as an aggregate, further study and participation in scientific forums as an aggregate, and profession training and participation in scientific forums as an aggregate on teachers’ performance, and analyzing the effectiveness of the teacher development management through those three activities. This study was a descriptive and explanatory survey. The results show all the three activities affect the teachers’ performance. This indicates that the teacher development program through those three activities is effective. Keywords: further study, profession training, scientific forums, performance